Setting Dengue Fever Epidemic Thresholds Between 2016 and 2021 in the Central Health Region, Burkina Faso: An Ecological Study - Jean Claude Romaric Pingdwindé Ouédraogo; Sylvain Ilboudo; Espérance Ouédraogo; Wendlasida Thomas Ouédraogo; Salfo Ouédraogo; Benoit Césaire Samadoulougou; Mikaila Kaboré; Léon G. Blaise Savadogo (Journal of Epidemiology and Global Health, 2023)
Abstract Background Dengue fever (DF) is endemic in Burkina Faso, with 70% of its burden supported by the Central Health Region. Then, a single confirmed case can no longer mean an epidemic. This study aimed at describing trends and setting epidemic thresholds of DF in the Central Health Region. Data and Methods An ecological study was conducted using monthly data from DF surveillance between 2016 and 2021. Three methods were applied to set alert and intervention thresholds of DF monthly incidence rate: mean [mean + 2 SD], median [3rd quartile] and cumulative sum (C-sum) [C-sum + 1.96 SD]. These thresholds were plotted with the monthly incidence rates for 2021. Results In total, 54,429 cases were reported between 2016 and 2021. Dengue cases increased biannually. The median annual incidence rate did not vary significantly across years [Kruskal–Wallis: χ 2(5) = 9.825; p = 0.0803]. Within a year, the monthly incidence rate fell under 48.91 cases per 100,000 inhabitants between January and September and peaked in October or November. With the mean and C-sum methods, the 2021 monthly incidence rate remained below the intervention thresholds (Mean + 2 SD and C-sum + 1.96 SD). With the median method, the incidence rate exceeded the alert and intervention thresholds in July–September 2021. Conclusions If the DF incidence varied within a year due to the seasons, it was relatively stable between 2016 and 2021. The mean and C-sum methods based on the mean were subject to extreme values, giving high thresholds. The median method seemed better for capturing the abnormal increase in dengue incidence.